EXPERIMENTAL-CLINICAL STUDIES OF PAIN CONTROL (3) : A MULTILATERAL EXAMINATION ON THE EFFECTIVENESS OF A SELF-MANAGED STRATEGY - HINO, SATORU; NEDATE, KANEO; AGARI, ICHIRO (Japanese Journal of Behavior Therapy, 1986)
The present study closely and multilaterally examined the effect of a strategy "watching self-managed comfortable slides" on pain control, taking individual differences of perceiving pain into consideration. Undergraduate male students were asked to immerse their dominant hands in the cold water, watching the comfortable slides which the subject himself managed (the experimental condition), or watching no such slides (the control condition). The major indices used to compare the effects of these two conditions were tolerance time, magnitude estimates (pain strength perceived at each point of time during hand immersion), and subjective ratings on the effectiveness of the strategy or no strategy. The results showed that the subjects were more successful in pain control under the experimental condition than under the control one in every major index, indicating that the strategy "watching self-managed comfortable slides" is extremely effective in pain control. This result was supported by the analysis in which individual differences of perceiving pain was taken into consideration. Future studies are expected to focus on exploring the intra individual factors which provide for these individual differences.